Howard Kreisel. Judaism as philosophy: Studies in Maimonides and the medieval Jewish philosophers of Provence>/i>. Boston: Academic Studies Press, 2015. 473 p.; 23,4 cm. ISBN 978-1-61811-179-1 (Emunot: Jewish Philosophy and Kabbalah) - i Pujol, Esperança Valls (TAMID. Revista Catalana Anual d’Estudis Hebraics, 2017)
Resenció de Howard KREISEL. Judaism as Philosophy: Studies in Maimonides and the Medieval Jewish Philosophers of Provence. Boston: Academic Studies Press, 2015. 473 p.; 23,4 cm. ISBN 978-1-61811-179-1 (Coŀl. Emunot: Jewish Philosophy and Kabbalah).